2012
DOI: 10.1080/08982112.2012.627288
|View full text |Cite
|
Sign up to set email alerts
|

Designed Experiments for the Defense Community

Abstract: The areas of application for design of experiments principles have evolved, mimicking the growth of U.S. industries over the last century, from agriculture to manufacturing to chemical and process industries to the services and government sectors. In addition, statistically based quality programs adopted by businesses morphed from total quality management to Six Sigma and, most recently, statistical engineering (see Hoerl and Snee 2010). The good news about these transformations is that each evolution contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Curiously, most case studies reported on scientific journals and textbooks on DoE do not illustrate the full sequential nature of an investigation. In many problems, the authors justify their approach to solve the problem, and use two out of three experimental phases, namely, screening/characterization [44] and screening/optimization [45]. A comprehensive example of the sequential learning process in the response surface methodology framework, including the optimization of multiple responses simultaneously, is presented by Lv et al [46].…”
Section: Doe's Principles and Experimentation Strategymentioning
confidence: 99%
“…Curiously, most case studies reported on scientific journals and textbooks on DoE do not illustrate the full sequential nature of an investigation. In many problems, the authors justify their approach to solve the problem, and use two out of three experimental phases, namely, screening/characterization [44] and screening/optimization [45]. A comprehensive example of the sequential learning process in the response surface methodology framework, including the optimization of multiple responses simultaneously, is presented by Lv et al [46].…”
Section: Doe's Principles and Experimentation Strategymentioning
confidence: 99%
“…Johnson et al present a number of military testing applications from a design of experiments perspective. For example, in Johnson et al, they discuss a five‐factor military force‐level encounter example and a seven‐factor air‐to‐air missile simulation example. In both experiments, the cost of experimentation is high.…”
Section: Application and Conclusionmentioning
confidence: 99%
“…The ability to relate the results to actual operations was provided through the use of a realistic mission scenario, and the use of current and qualified weapon system operators in the experiment. This experiment also adhered to an accepted factorial design [7] process.…”
Section: Trialmentioning
confidence: 99%